Multimessenger study of baryon-charged QCD matter in heavy-ion collisions - Lipei Du (Physics Letters B)
Multimessenger studies of heavy-ion collisions, using hadrons and electromagnetic probes, can reveal the properties of the created QCD matter from different perspectives. This study calculates the thermal dilepton invariant mass spectra and thermal photon transverse momentum spectra in Au+Au collisions at low beam energies from the Beam Energy Scan program, using a (3+1)-dimensional multistage hydrodynamic model calibrated by rapidity-dependent hadronic distributions. The effects of thermodynamic rapidity variation, baryon chemical potential, and fluid expansion on the spectra are explored. Methods for extracting temperature from photon and dilepton spectra are examined by comparison with the underlying hydrodynamic temperature. The possibility of combining photon and dilepton spectra to extract radial flow is also investigated. This study provides insights into measuring the thermodynamic properties of the created systems in heavy-ion collisions using multiple messengers through two fundamental interactions within the same framework.